2009
DOI: 10.1152/ajpendo.00080.2009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of glutathione and ophthalmate traced with2H-enriched body water in rats and humans

Abstract: of glutathione and ophthalmate traced with 2 H-enriched body water in rats and humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 33 publications
1
42
1
Order By: Relevance
“…An increasing number of studies have suggested that OPH could be a marker of hepatic GSH depletion [4][5][6][9][10][11]. However, most of these data are derived from animal experiments and human OPH data are scarce.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increasing number of studies have suggested that OPH could be a marker of hepatic GSH depletion [4][5][6][9][10][11]. However, most of these data are derived from animal experiments and human OPH data are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of these data are derived from animal experiments and human OPH data are scarce. Kombu et al [6] investigated the GSH-OPH system by labelling free GSH, bound glutathione (GSSG) and OPH following intravenous infusion of 2 H-enriched water and subsequently used an LC-MS-MS assay to determine enrichments. This method provided the opportunity to measure the synthesis of these components in rat plasma, erythrocytes and liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 C-lysine) is that numerous protein-bound nitrogens will be labeled, therein increasing the window when measuring shifts in the isotope distribution of a proteolytic-peptide. A final approach to label the precursor pool centers on the administration of labeled water, either 2 H 2 O or H 2 18 O ( Figure 4C) (Cabral et al 2008;De Riva et al 2010;Kombu et al 2009;Rachdaoui et al 2009;Xiao et al 2008). The rationale is that cells will generate labeled amino acids in the presence of labeled water, e.g.…”
Section: How Can I Label the Precursor Pool?mentioning
confidence: 99%
“…Despite the fact that studies based on the use of labeled water revolutionized our understanding of metabolic biochemistry nearly 80 years ago there appears to have been a dramatic shift away from the use of labeled water in the field of protein dynamics for reasons that remain unclear (Borek, Ponticorvo, and Rittenberg 1958;Schoenheimer and Rittenberg 1938;Ussing 1938;Ussing 1941;Ussing 1980). We, and others, have recently revisited the use of 2 H 2 O in studies of protein synthesis (Busch et al 2006;Cabral et al 2008;De Riva et al 2010;Kombu et al 2009;Previs et al 2004;Rachdaoui et al 2009;Xiao et al 2008), we also recognized the potential advantage(s) of using H 2 18 O (Bernlohr 1972;Bernlohr and Webster 1958;Borek, Ponticorvo, and Rittenberg 1958;Rachdaoui et al 2009;Rittenberg, Ponticorvo, and Borek 1961). Our use of H 2 18 O was based on a classical study in which Rittenberg and colleagues demonstrated that H 2 18 O could be used to study protein synthesis (the outstanding contributions of Bernlohr and others further tested the approach and more clearly outlined the logic) (Bernlohr 1972;Bernlohr and Webster 1958;Borek, Ponticorvo, and Rittenberg 1958;Rittenberg, Ponticorvo, and Borek 1961).…”
Section: How Can I Label the Precursor Pool?mentioning
confidence: 99%